Identyfikacja i wycena prywatnych korzyści z kontroli - Kałdoński, Michał; Mizerka, Jacek (Identification and Valuation of Private Benefits of Control, 2007)
The paper concerns the problem of valuation of private benefits of control. By the private benefits of control we mean every situation in which some value, whatever the source, is not shared among the shareholders in proportion of the shares owned, but it is enjoyed exclusively by the party in control. He problem of valuation of private benefits of control we treat as the problem of valuation of possibility of choice of an ownership structure. We confront the concentrated structure of ownership (private company) with dispersed (public company). For the purpose of valuing private benefits of control, we use the model of valuing an option to switch proposed by Kulatilaka and Trigeorgis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 173-185